Judicial Considerations in Imposing Sentences on Children Who Commit Crimes of Maltreatment (Decision No. 14./Pid.Sus.Anak/2021/PN.Mdn) - Sinabutar, Sartika Domuria Silalahi; Marlina, Marlina; Trisna, Wessy (Dinasti Research, 2025)
Law enforcement against children in conflict with the law (CICL) has unique characteristics compared to adults, as regulated under Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This study aims to analyze the judges' considerations in imposing sanctions on a child perpetrator of an assault crime based on Decision Number 14/Pid.Sus.Anak/2021/PN.Mdn. The research method employed is normative juridical with a statutory and case approach, focusing on the court's decision analysis. The results indicate that the judges’ considerations include juridical, sociological, and psychological aspects, such as the offender's age, family condition, the impact on the victim, and the objectives of the child's rehabilitation. The judge imposed a sentence by prioritizing the principle of the best interests of the child, restorative justice, and social reintegration efforts. However, there remain concerns regarding the consistency of the ruling with child protection principles, particularly concerning the effectiveness of rehabilitation and coaching programs. This study recommends that juvenile courts prioritize diversion as an alternative to formal court proceedings and optimize child rehabilitation institutions in accordance with applicable laws.